Entomological assesment of Wuchereria bancrofti transmission following mass treatment in Gampaha District, Sri Lanka. - Wijegunawardana, N.D.A.D.; Gunawardene, Y.I.N.S.; Abeyewickreme, W. (Faculty of Tropical Medicine, Mahidol University, 2007)
Global program to eliminate Lymphatic filariasis (Lf) relies mainly on Mass Drug Administration (MDA). Success of filariasis control programs depends on careful monitoring of infection levels in human populations as well as vectors following the introduction of the drug intervention. This study was conducted to assess the current level of Lf transmission following mass distribution of Diethylcarbamazine-Albendazole in the Gampaha district, Sri Lanka. Field study was conducted in 45 sites in all Medical Officer of Health (MOH) areas of the Gampaha district identified by the Anti Filariasis Campaign (AFC) as high risk for bancroftian filariasis. Investigation revealed 42.22% (19/45) of the sites were infested with mosquitoes positive for Wuchereria bancrofti. Only the sites in urban and semi urban areas were positively infested while rural areas were free of infection. An infection rate of 5.26% was observed among the mosquitoes caught from households and the larval density was 8.7 per positive mosquito. According to a study conducted by the AFC in a sample population (14 sites), the prevalence of Lf was 0.038%. Data recorded by the AFC in 1994 indicated that the infective rate, positivity of mosquitoes and microfilaria density were 90%, 3.05% and 23 respectively. The present study confirms that the level of transmission of W. bancrofti has not decreased in the Gampaha district, despite the MDA Programme been implemented since 2002. Therefore, a proper screening-programme combined with anti filarial treatment and. vector control programme is urgently required to minimize filarial morbidity and interrupt filarial transmission within the country.
Oral Presentation of Joint International Tropical Medicine Meeting (JITMM 2007), 29-30 October 2007 Bangkok, Thailand
Keywords: Filariasis; Wuchereria bancrofti; Elephantiasis, Filarial; Filariasis-drug therapy; Filariasis-prevention and control